Knowledge Level of Emergency for Students at Senior High School Al-Azhar Asy Syarif Islamic Boarding School Deli Serdang - Lubis, Andriamuri Primaputra; Khairani, Mitra (Talenta Publisher, 2023)
Background: Emergency means life threatening, while emergency is the need to get immediate treatment or action to eliminate the threat to the victim's life. Emergency is a condition when patient's clinical condition requires immediate medical action to save lives and prevent disability. In handling emergency cases, taking the right action for help must be carried out quickly, precisely, and calmly. This study is a cross sectional study. Data was collected in the form of a questionnaire. Questionnaires were collected twice, first the pretest which was carried out before the instructor gave the emergency material and the posttest which was carried out after the emergency material was given. The results show that in general, the posttest results show a shift to a higher score than the pretest results. Conclusion The level of knowledge of students at MA Al-Azhar Asy Syarif Islamic Boarding School Deli Serdang regarding emergencies, is categorized as Good.